Development of descriptors for domains and items for collective participation in occupations - Adams, Fasloen (My University, 2016)
The intention of this study was to develop domains, items and descriptors for levels of collective participation, which can be used as guidelines by occupational therapists to determine a collective’s ability to participate in collective occupations. These developed levels aimed to increase therapists’ understanding of the collective’s occupational potential, enabling better planning of more appropriate, preventative and promotive health programmes. A mixed methods approach and a sequential exploratory design were used to complete this study. The study consisted of three phases. Phase one used a qualitative approach and a descriptive design to explore and conceptualise collective occupation and participation in collective occupations. The phase consisted of two stages. Stage one conceptualised collective occupations from the perspectives of South African occupational therapists. Data were gathered through eleven semi-structured interviews. Stage two focused on the conceptualisation of collective occupations from profession-specific literature. Data were gathered through a literature review. Phase two focused on the development of the domains and items for the understanding of collective participation using the information gained from the interviews (stage one in phase one) and from the review of the literature (stage two in phase one). This phase also consisted of two stages. In stage one, domains and items for collective participation were developed. In stage two, descriptors for each domain and item on seven levels of collective participation were developed. In this phase, five domains - motivation, action, relations, product and emotional functioning - were developed and each of these domains has associated items. In stage two of this phase, descriptors for each item on seven sequential levels of collective participation in occupation were developed. The Vona Du Toit Model of Creative Ability was used to provide structure and to guide the development of domains, items and item descriptors. Lastly, phase three focused on the content validation of the domains, items and descriptors developed in the previous phase. In this phase, item content validity, as well as scale content validity, was established. Results from this phase found that the scale as a whole, the domains and items were valid. The majority of the items descriptors on the sequential levels were also found to be valid with only ten items being rated as invalid by a panel of experts. In conclusion, descriptors for seven levels of collective participation were developed through this research. The newly developed levels of collective participation are now ready for conversion into an assessment tool, psychometric investigation and field-testing. These descriptors of collective participation could help occupational therapists to understand the behaviour and the potential of collectives, which in turn could aid in harnessing the effectiveness of collectives and thus passively influence the health and well-being of collectives.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor in Philosophy Johannesburg, 2016
Keywords: Occupational Therapist